Transcriptomic Analysis of Seed Germination Under Salt Stress in Two Desert Sister Species (Populus euphratica and P. pruinosa) - Zhang, Caihua; Luo, Wenchun; Li, Yanda; Zhang, Xu; Bai, Xiaotao; Niu, Zhimin; Zhang, Xiao; Li, Zhijun; Wan, Dongshi (Frontiers in Genetics, 2019)
Soil salinity is tone of the most major abiotic stress limiting germination, plant growth, development and production. The seed germination is highly related to seedling survival rate and subsequent vegetative growth. Populus euphratica and P. pruinosa are closely related species and show distinguished adaptability to salinity stress. To reveal the physiological and molecular mechanisms controlling poplar species seed germination under salt stress, transcriptome analyses were performed in three seed germination phases from P. euphratica and P. pruinosa with different salt sensitivity. The two-dimensional date set provides a comprehensive view on dynamic biochemical processes transition underpinning seed germination and salt tolerance. Our analysis identified 12831 DEGs (Differentially Expressed Genes) for seed germination processes, and 8071 DEGs for salt tolerance variety of the two species. Furthermore, we identified expression profiles and the main pathways for each phases. For seed germination, a large number of DEGs including those involved in energy production and hormonal regulation pathways were transiently and specifically induced in the late phase. For salt tolerance between the two species, the flavonoid and brassinosteroids pathways were significantly enriched. More specifically, in the flavonoid pathway, FLS and F3’5’H exhibited significantly different expression. In the brassinosteroids pathway, DWF4, BR6OX2 and ROT3 exhibited significantly higher expression in P. pruinosa than in P. euphratica. Our results describe transcript dynamic, and highlight second metabolites pathways involved in the response to salt stress during seed germination of two desert poplars.